Struktur Komunitas Mangrove di Pesisir Pantai Kecamatan Sedati dan Kecamatan Jabon Kabupaten Sidoarjo - Purity Sabila Ajiningrum; Muhammad Anugrah Dewangga (UNIVERSITAS PGRI MADIUN, 2022)
Sidoarjo is a district that has a mangrove ecosystem, but due to the rapid development in Sidoarjo, there is a lot of conversion of mangrove land into residential land. Therefore, it is necessary to collect data on mangroves in the Coastal of Sedati District and Jabon District, Sidoarjo Regency. The purpose of this study was to determine the index of diversity value and the index of importance of mangroves on the coast of Sedati and Jabon sub-districts, Sidoarjo district, with a trans-sect line plot of 10Ã—10 along 300 meters perpendicular to the shoreline at 2 predetermined observation stations. Observational data were analyzed with the Shannon-Weiner diversity value index and the significance value index. Based on observational data, the diversity index obtained is 0,942 and the value of H' is less than 1, indicating that the diversity index on the coast of Sedati District and Jabon District, Sidoarjo Regency is low. The important value index on the coast of Sedati District and Jabon District, Sidoarjo Regency is 298.058% for trees and 22.02% for seedlings, and Avicennia marina has the highest important value index with a value of 198.25. Environmental conditions at station 1 in Sedati District showed unfavorable environmental conditions for the distribution of various types due to the high thickness of the mud, causing some species to have difficulty adapting, but at observation station 2 in Jabon District it supported the distribution because it had a medium to thin mud thickness so that various species adaptable.